Impact of Oncoming Headlight Glare With Cataracts: A Pilot Study - Hwang, Alex D.; Tuccar-Burak, Merve; Goldstein, Robert; Peli, Eli (Frontiers in Psychology, 2018)
Purpose: Oncoming headlight glare (HLG) reduces the visibility of objects on the road and may affect the safety of nighttime driving. With cataracts, the impact of oncoming HLG is expected to be more severe. We used our custom HLG simulator in a driving simulator to measure the impact of HLG on pedestrian detection by normal vision (NV) subjects with simulated mild cataracts and by patients with real cataracts. Methods: Five NV subjects drove nighttime scenarios under two HLG conditions (with and without HLG; HLGY/HLGN), and three viewing conditions (with clear, simulated cataract, and optically blurred clip-on; NO/SC/OB). Each scenario contains pedestrian encounters, where pedestrians appearing on the left or right sidewalk, either walking in the same direction as the subject car or crossing the road. Pedestrian detection performances of five patients with mild real cataracts were also measured using the same setup. Participants’ visual acuity and contrast sensitivity were also measured in the simulator with and without stationary HLG. Results: Both the presence of oncoming HLG and wearing the SC clip-on reduced pedestrian detection performance for NV subjects. The subjects performed worst in the pedestrian crossing-from-left events followed by crossing-from-right events. Significant interactions were also found: 1) the negative impact of HLG was larger with SC clip-on than with NO clip-on, 2) the impact of HLG was larger with OB clip-on than with NO clip-on, but smaller than with SC clip-on, and 3) the impact of HLG was larger for crossing events, suggesting that the pedestrian proximity to the glare source was the major contributor to the performance reduction. The presence of HLG increased the number of pedestrian misses and untimely response, more with SC clip-on than with NO clip-on. The impact of HLG measured for the real cataract patients was similar to that of NV subjects with SC clip-on. Conclusions: Even with mild (simulated or real) cataracts, a substantial negative impact of oncoming HLG was measurable in the detection of crossing/walking pedestrians. The lowered hazard detection rate and longer response time with HLG demonstrated the possible risk that oncoming HLG can pose to pedestrians by patients driving with cataract.